Advancing user-centric design and technology adoption for aging populations: a multifaceted approach - Stamate, Andreea; Marzan, Mircea-Dan; Velciu, Magdalena; Paul, Cosmina; Spiru, Luiza (Frontiers in Public Health, 2024)
The global demographic shift toward an aging population necessitates a nuanced approach to developing and adopting assistive technologies tailored for older adults. This paper synthesizes key challenges, strategies, and recommendations identified in addressing the complex landscape of technology adoption and usage among aging populations. User-centric design and co-creation initiatives are vital for developing assistive technologies that meet the needs of older adults. These initiatives involve engaging older adults in activities like workshops, focus groups, and design sessions to gather feedback and refine technology solutions, ensuring they are accessible, intuitive, and effective. Challenges such as participant selection, cultural attitudes, and trust-building mechanisms are paramount in ensuring meaningful user involvement in technology development processes. Accurate assessment of older adults’ technological literacy is identified as critical for designing and implementing digital solutions. The unreliability of self-reported proficiency necessitates objective measures in assessments to counter potential biases and ensure accurate insights into user capabilities. The fragmented digital ecosystem and resulting digital divide among older adults pose significant barriers to technology adoption and usage. The role of caregivers in technology acceptance highlights the need for integrated models that encompass the caregiver perspective, reducing adoption barriers and fostering meaningful engagement with assistive technologies. Interdisciplinary collaboration and robust research standards are essential in advancing technology adoption and addressing societal inequalities. Prioritizing user-centric design, integrating caregivers into technology adoption models, and fostering collaborative efforts across disciplines can significantly improve technology acceptance and enhance the quality of life for older adults in an increasingly digital era.